The Application of Dextran Sedimentation as an Initial Step in Neutrophil Purification Promotes Their Stimulation, due to the Presence of Monocytes - Alex Quach; Antonio Ferrante (Journal of Immunology Research)
The purification of human neutrophils for in vitro studies is challenging as they are easily activated through ex vivo manipulations. The technique of erythrocyte sedimentation combined with density gradient centrifugation remains widely practiced and was the subject of this study. Since in the sedimentation step the leukocytes are incubated with dextran, we have raised the likelihood that cellular activation would occur with mediator release leading to neutrophil activation. By comparing the activity of neutrophils purified from whole blood by the classical 2-step method of dextran sedimentation followed by low-density Ficoll-Hypaque (1.077 g/mL) medium, and the 1-step high-density Ficoll-Hypaque (1.114 g/mL) gradient centrifugation, we found that neutrophils from the 2-step method had a significant increase in cell surface CD11b expression and CD62L shedding and a marked increase in adhesion. Decreased random migration and chemotaxis and raised baseline oxidative burst activity were also observed. The effect was not specific to dextran, as using Ficoll for erythrocyte sedimentation replicated the elevated neutrophil adherence. Through the depletion of monocytes, lymphocytes, and platelets prior to sedimentation, we deduced that monocytes were responsible for the neutrophil activation. Our findings suggest that care needs to be exercised in choosing the method of neutrophil purification for functional studies.